STRATEGIC RESOURCE MANAGEMENT: FIXING THE MISSING CHAIN IN THE COMMERCIALIZATION OF UZBEK UNIVERSITY RESEARCHES - Ismoilov Elyorjon Makhamadali Ugli, (TADQIQOTLAR, 2026)
Abstract. The study investigates the strategic resource management of academic intellectual  property,  aiming  to  explore  the  transition  mechanisms  for  the commercialization of university researches in the Republic of Uzbekistan. By utilizing the  Resource-Based  View  (RBV)  logic  and  qualitative  assessment  of  the  VRIO framework,  the  analysis  reveals  a  significant  gap  in  the  strategic  orchestration  of academic  knowledge,  but  exposes  an  “innovation  productivity  paradox”  in  the emerging digital economy. The high concentration of raw scientific publications is negatively  correlated  with  actual  startup  ecosystem  integration,  reflecting  the dominance  of  isolated  academic  practices  over  market-driven  innovation.  Besides, institutional  landscapes  revealed  a  critical  deficit  in  the  organizational  capacity necessary to exploit valuable resources. To meet the ambitious targets of the “Digital Uzbekistan  -  2030”  strategy,  there  is  a  necessity  of  fixing  the  “missing  chain”-specifically, intermediary technology transfer mechanisms-extracting crucial lessons from strategic resource orchestration to transform academic potential into sustained competitive advantage.